Tipologias de realização e circulação no cinema do Rio Grande do Sul : um estudo sobre os longas-metragens mulher do pai e rifle - Swirsky, Victória Godolfim (2019)
The main objective of this research is to analyze the processes of production and circulation of the films Mulher do Pai (Cristiane Oliveira, 2016, Okna Produções) and Rifle (Davi Pretto, 2016, Tokyo Filmes) in order to better understand decisions made during the development process of these projects that influenced their placement in the international festival circuit, identifying recurrent characteristics of this realization model. The selection of the films had as criteria their similarities regarding shooting locations, their similar interval between realization and launch, and their circulation. Using the case study methodology proposed by Yin, we aimed to analyze the circulation strategies of these films. This study is based on Metz's statements on the differentiation of filmic fact and cinematic fact as a justification to approach aspects beyond-film, and not symbolic aspects. Barone’s propositions regarding the structure of the film market and relations between the agents inherent to to realization were used to establish the context in which the corpus of this dissertation is inserted. The theoretical basis for film selection was the concept of exportation films presented by Chalupe. Using the foundations of empirical research, the executive producers of the feature films studied reported their experience working on the films to support the analysis. We also had access to the production documents. This dissertation proposed, in its conclusion, a typology of production common to both films, placing them in the cinematic industry based on its goals and strategies of production and circulation.